Satisfaction of medical students with the artistic anatomy lecture: A questionnaire study - Karaca Bozdağ, Zekiye; Çandır Gürses, Buse Naz (The European Research Journal, 2025)
Objectives: The aim of this study is to evaluate the effects of an artistic anatomy lecture on medical students and to identify the role of the lecture in education. Methods: A 20-question online satisfaction survey was administered to 32 out of 45 medical students who attended the artistic anatomy lecture at our university in the fall semester of 2023-2024. In the survey, questions were asked to reveal the students' performance regarding the relationship between art and anatomy. SPSS Statistics 22 software (IBM SPSS, Turkey) was used for statistical analysis of the data obtained, and P